Evaluasi Implementasi Kebijakan Sertifikasi Kelaiklautan Kapal di Kantor Kesyahbandaran dan Otoritas Pelabuhan (KSOP) Bitung - Majumi Amelia Kerenafuk Mamuaja; Jeane Elisabeth Langkai (Civic Education: Media Kajian Pancasila dan Kewarganegaraan, 2023)
Following up on demands for the seaworthiness of ships described in the shipping law, the Minister of Sea Transportation issued a Minister of Transportation Regulation Number PM 110 of 2016 concerning Ship Safety Inspector Officers. Factors causing ship accidents are the non-fulfillment of ship safety and seaworthiness standard requirements in accordance with statutory provisions and government regulations or policies that have been stipulated. This study aims to reveal the implementation of the ship's seaworthiness certification policy and the determinants of the implementation of the ship's seaworthiness certification policy. This study used qualitative methods using observation and interviews as data collection methods. The results of this study indicate that the implementation of the ship's seaworthiness certification policy based on the focus studied is the size and objectives of the policy, human resources, KSOP commitment, PKKK officials, KSOP have a good relationship with ship operators, and obstacles to obtaining a seaworthiness certificate. The determinants of the implementation of ship seaworthiness certification policies are the attitude of the implementer, communication and coordination between agents, and sources of funds